The struggle of Rashid Rida in Pan-Islamism movement - Siti Nurul Izza Hashim,; Ermy Azziaty Rozali, (Institut Kajian Rantau Asia Barat, 2013)
Rashid Rida was a prominent Muslim reformer at the end of the 19th century and early 20th century. His struggle in the Pan-Islamism movement and the institution of the Caliphate was to defend and liberate the Muslims from Western colonialism. This article put forth the general struggle Rashid Rida against Western colonialism. This article also discusses briefly the history of the idea of Pan-Islamism and the institution of caliphate. This study which used the content analysis, and historical methods showed that Rashid Rida had exceptional qualities with the publication of his work, entitled Tafsir al-Manar which is based on the Quran. This work had a profound impact on the intellectual development among local scholars, especially of Young People. The importance of this study is particularly relevant because the stature and influence of his thought, has spread throughout the Islamic world as well as a significant impact in many areas, particularly in politics.